(untitled) (Research, Society and Development, 2022)
The theme chosen for this paper is "abuse clauses in adhesion contracts", and the main objective is to verify the reasons for the use of abuse clauses in adhesion contracts. The supplier drafts the contract, and the consumer has only the option of accepting or not accepting the contract, and when the contract is accepted, to represent conformance with the content of the contract. The advantages of adhesion contracts are that they promote the simplification of negotiations, and the clauses are ready, so that deliberation can be avoided, saving time. Therefore, since the generally applicable law is the law of the strongest, there are institutional defects in the practice that can harm the most vulnerable in the contractual relationship. In this way, compliance with this modality could favor abusive clauses, and the imposition of conditions that compromise the integrity or balance of the services provided by the parties. It is up to the Consumer Code to reserve rights, protect consumers and determine equity in the fulfillment of the contractual relationship.